Assessment of Heavy Metal Content of Njere River in Umuakam, Okaiuga Nkwoegwu, Umuahia North L.G.A - , D. Akachukwu, U. Mbakwe, I. A. Okoro (Archives of Current Research International, 2017)
Aims: To assess the heavy metal content of water from Njere river in Umuakam Okaiuga Nkwoegwu autonomous community in Umuahia North L.G.A of Abia State. Study Design: Purposive sampling was employed for sample collection. Place and Duration of Study: Department of Chemistry, Michael Okpara University of Agriculture, Umudike from June 2009 to December 2009. Methodology: Water samples were collected from upstream, midstream and downstream locations of the Njere river. From each location, water was collected from three different points and combined to form a composite. The total, soluble and exchangeable metal ions were estimated by the use of Atomic absorption spectrophotometer. Results: Total Nickel, cadmium and zinc ion content exceeded the WHO standard in all the locations. Water soluble zinc ion was higher than the standard for all the samples. Exchangeable metal ions exceeded the standard for Ni, Cd, Zn and Pb. Conclusion: The water from the Njere river is not completely safe for domestic and agricultural activities.